STRENGTHENING INTERNATIONAL COMPETITIVENESS AND INVESTMENT GROWTH AS THE BASIS FOR A NEW MODEL OF SERBIAN ECONOMY DEVELOPMENT - Đurić, Dejan; Mitrović, Vladimir; Đurić, Dragana; Ristić, Jelena (Economics of Agriculture, 2018)
Insuffcient export activity and low level of investment in the formation of gross domestic product are a negative feature of the Serbian economy over a longer period of time. The global fnancial and economic crisis has shown that a sustainable model of economic growth, which was basically based on the growth of domestic consumption and imports and a low share of investments in the structure of the use of GDP, is an unsustainable until then. It has become clear that such a model must be replaced by a pro-investment and export-oriented model of economic growth. Bearing in mind the trends in macroeconomic flows in the Serbian economy, it is clear that the increase in investment and the competitiveness of domestic production imposes itself as one of the most important tasks of economic policy in the future. In this sense, the main goal of this.